DISEMINASI TEKNOLOGI DETEKSI KEBUNTINGAN DINI “DEEA GESTDECT” TERHADAP SAPI POTONG DI KINALI KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful (LPPM Universitas Andalas, 2018)
The West Pasaman area is an area that has a large enough potential for plantation and agricultural land. Kinali is one of the nagari in Pasaman Barat with an area of 489.64 km₂ is one of the nagari in this Regency which has a large carrying capacity of land and has the potential to develop cattle breeding business. Community service activities are carried out with the aim of providing information to farmers and the public about optimizing the use of